COMMUNICATIVE ROLE OF NON-STANDARD ENGLISH SUCH AS SLANG - Erkinova Aziza Erkin qizi (International Journal on Integrated Education, 2023)
Nowadays, most people think that studying a foreign language is quite important. Most people in the world are learning languages as a second language, English in particular. However, learning a language is not merely memorization of vocabulary; it also requires familiarity with colloquial English and its varieties, or "slang." And slang is considered a part of modern language.